OPTIMASI KEUNTUNGAN PRODUKSI MAKANAN DENGAN METODE SIMPLEKS BERBASIS POM-QM FOR WINDOWS (Studi Kasus: UMKM Bakmi & Nasi Goreng Jowo Mas Narto) - Abduh Riski; Agustina Pradjaningsih; Durratul Sayyidah Adilah Munawaroh (Prodi Matematika FMIPA Unirow Tuban, 2025)
Micro, Small, and Medium Enterprises/UMKM are some of the businesses that have an important role in developing the economy in Indonesia. Bakmi and Nasi Goreng Jowo Mas Narto is one of the UMKM engaged in culinary in the Jember area. Based on the results of interviews conducted with owners, sales fluctuate in food production, thus making the profit of food sales not always predictable. Thus, this study aims to provide a solution for optimizing the benefits of food production with the simplex method using POM-QM for Windows. The results of this research show that these MSMEs will get optimal profits if they produce food, namely 50 portions of fried rice, 43 portions of fried noodles, 8 portions of fried vermicelli, and 8 portions of letek noodles with a profit of Rp 438,095 in a day.